2014
DOI: 10.1007/s11655-014-1760-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical evaluation of response to treatment of Parkinson’s disease with integrated Chinese and Western medicine therapy

et al.

Abstract: The six assessed means of clinical evaluation (including UPDRS II and UPDRS III scores, sleep scale score, getting up time, 10 m×2 times, and turning time) are sensitive indexes in all PD patients. H-Y stage and Madopar dosage are the major factors influencing means of clinical assessment of PD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In addition to activate Nurr1 by recognition on the specific target region of Nurr1, some other compounds, such as DA agonists, memantine, retinoic acid-loaded polymeric nanoparticles (RA-NPs) and herbal extracts (as summarized in Table 2), have also been demonstrated to up-regulate Nurr1 expression in preclinical trials of PD treatment although there have not any report to confirm that they can activate Nurr1 by direct binding [63, 66, 7073, 78]. …”
Section: Nurr1 Modulatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to activate Nurr1 by recognition on the specific target region of Nurr1, some other compounds, such as DA agonists, memantine, retinoic acid-loaded polymeric nanoparticles (RA-NPs) and herbal extracts (as summarized in Table 2), have also been demonstrated to up-regulate Nurr1 expression in preclinical trials of PD treatment although there have not any report to confirm that they can activate Nurr1 by direct binding [63, 66, 7073, 78]. …”
Section: Nurr1 Modulatorsmentioning
confidence: 99%
“…Besides those chemically synthesized compounds, several Nurr1-modulators from natural source, such as moracenin D, EGb 761, radicicol and Bushen Huoxue Decoction (BHD), are also effective in PD therapy [7073]. Moracenin D, an extract from Mori Cortex radices, significantly up-regulates Nurr1 expression and down-regulates α-synuclein expression [70].…”
Section: Nurr1 Modulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, H-Y stage and age were predictive of the effects of integrated Chinese and western therapy as evaluated using the UPDRS III score. 11 The authors thus hypothesize that the severity of PD is a determinant of EA treatment response. Another subgroup analysis revealed that participants with tremor type PD did not improve following treatment.…”
Section: Comment/critiquementioning
confidence: 99%